Enhancing irradiation tolerance and inducing superlubricity in MoS2/W multilayer film exposed to atomic oxygen - Xin Fan; Wenhao He; Zhenao Zhang; Bo He; Yanwen Lin; Qinsheng He; Liang-Feng Huang; Siming Ren; Zhibin Lu; Jibin Pu; Qunji Xue (Communications Materials)
Abstract Molybdenum disulfide (MoS2) is a ubiquitous lubricant for use in outer space. Here, we present a MoS2/W nano-multilayer film engineered through precise structural optimization by fine-tuning sputtering parameters. This architecture, featuring alternating metallic W layers and highly oriented MoS2 layers, restricts oxidation depth to less than 25 nm (2.7×1021 atoms·cm−2)—just one-23rd of that observed in composite structure—outperforming previously reported space lubricants. Intriguingly, the metal oxide nanoparticles formed during atomic oxygen irradiation further reduce friction, enabling robust superlubricity with a friction coefficient of ~0.008. Our approach, bolstered by theoretical calculations and experiments, elucidates that this achievement is facilitated by the dual strengthening of the nano-multilayer structure and the in-situ generation of high-concentration, small-sized oxide nanoparticles at the contact interface. These findings provide invaluable insights into the design of irradiation-resistant and durable lubricating materials for space applications.